Predicting Consumer Green Product Purchase Attitudes and Behavioral Intention During COVID-19 Pandemic - Chen, Xia; Rahman, Muhammad Khalilur; Rana, Md. Sohel; Gazi, Md. Abu Issa; Rahaman, Md. Atikur; Nawi, Noorshella Che (Frontiers in Psychology, 2022)
This work has aimed to investigate the consumers’ green product purchase attitudes and behavioral intention during COVID-19 pandemic. Data was collected through a survey method of 503 consumers in Malaysia. Data were analyzed using the partial least square method. The findings revealed that fear of COVID-19 pandemic has a significant impact on green product behavioral intention. Green product literacy, green product orientation, and social influence have a significant influence on green product purchase attitudes. The results also indicated that consumers’ green product purchase attitudes mediate the effect of green product literacy, green product orientation, and social influence on behavioral intention. The findings of this work will provide strategically relevant references to green marketers and retail managers in the understanding of consumers’ green product purchase attitudes and green product behavioral intention during the ongoing uncertainty of the COVID-19 pandemic.